THE MEDIATING ROLE OF EMOTIONAL INTELLIGENCE ON JOB STRESS AND EMPLOYEE PERFORMANCE - Gabriella Panjaitan; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
This critical review examines the mediating role of emotional intelligence (EI) in the well-established relationship between job stress and employee performance. While the direct negative impact of stress on performance is well-documented, this article synthesizes existing literature to argue that EI acts as a crucial psychological buffer in this dynamic. The analysis differentiates between ability and trait models of EI and elucidates the